Variations in root system architecture and root growth dynamics of Brassica rapa genotypes using a new scanner-based phenotyping system - Adu, Michael Osei (2014)
There is a need to breed for root systems architectures (RSAs) that optimise soil resource acquisition. This requires high resolution and high-throughput quantification of RSA in as natural an environment as possible. Current imaging techniques are limited by cost, reproducibility, throughput and complexity. This thesis describes (1) the construction of a low cost, high-resolution, root phenotyping platform that requires no sophisticated equipment which is adaptable to most laboratory and glasshouse environments and (2) its application to quantify environmental and temporal variation in RSA between genotypes of Brassica rapa L.